Fluid Russia : between the global and the national in the post-Soviet era - Michlin-Shapir, Vera (NIU series in Slavic, East European, and Eurasian studies., 2021)
"This book contextualizes Russian national identity in the global era and in late modernity. Exploring the formation of citizenship, discourse, and holiday practices, it demonstrates the profound impact of globalization on life in Russia and on the new and flexible experience of Russianness that was shaped in this process"--